Design of front-end receiver for low noise ultrasound imaging system - Sun, Huaxi (2017)
Ultrasound imaging has been widely used in industrial and biomedical applications. In general, high sensitivity of the front-end system is always wanted. The way of increasing the sensitivity is to increase the input signal and reduce the noise figure (NF) of the system that is dominated by NF of the first stage. Therefore the ultrasound transducer, the low noise amplifier (LNA) and the matching network between them are studied, resulting in the conclusion that conventional matching techniques are insufficient for voltage amplification or noise optimization.